THE INFLUENCE OF ENGLISH READING ATTITUDE ON STUDENTS’ READING COMPREHENSION - Peni Septianingsi; Yunani Atmanegara (Universitas Tridinanti Palembang, 2021)
Attitude in reading the English texts drives students to have enjoyable or unpleasing reading practice and affects the final result. This study intended to look for the influence of English reading attitude along with its aspects on students' reading comprehension. It also attempted to figure out which aspect of reading attitude contributed to reading comprehension. This study was conducted using correlation method. The population was the tenth grade students of an Islamic Senior High School in Palembang. The total sample participated was118 students selected by using cluster random technique. The data collection technique used reading attitude questionnaire and reading comprehension test. After analyzing the data using correlation and regression analysis, it was found that there was a significant correlation between reading attitude and reading comprehension. Though the correlation was in low category, reading attitude gave contribution to reading comprehension. For the aspects of reading attitude, cognitive attitude, negative affect, and self-assessment significantly correlated to reading comprehension. However, only negative affect showed its contribution. It indicates that English reading attitude influenced reading comprehension in positive way but only in small portion. Students could recognize the importance of reading English text for their language improvement and future success. However, poor reading comprehension skill obstructed them to have more practice in reading. The negative feelings about reading materials block students to achieve comprehension on the subject matter.Keywords: reading attitude, reading comprehension